2011
DOI: 10.1161/circresaha.111.240150
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-133 Controls Vascular Smooth Muscle Cell Phenotypic Switch In Vitro and Vascular Remodeling In Vivo

Abstract: Key Words: vascular smooth muscle cells Ⅲ microRNA Ⅲ miR-133 Ⅲ smooth muscle differentiation Ⅲ vascular remodeling V ascular smooth muscle cells (VSMCs) within adult blood vessels proliferate at a very low rate, exhibit very low synthetic activity, and express a unique repertoire of contractile proteins, ion channels, and signaling molecules. 1 Unlike skeletal muscle and cardiac muscle, which consist of terminally differentiated cells, adult VSMCs retain remarkable plasticity and can undergo rather profound an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
237
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(249 citation statements)
references
References 31 publications
8
237
0
1
Order By: Relevance
“…38 and 39). It is enriched in cardiac myocytes (40) and vascular smooth muscle cells (41). In each instance, miR133 appears to play an important role suppressing cell growth (42,43) and expression of extracellular matrix constituents (44).…”
Section: Discussionmentioning
confidence: 99%
“…38 and 39). It is enriched in cardiac myocytes (40) and vascular smooth muscle cells (41). In each instance, miR133 appears to play an important role suppressing cell growth (42,43) and expression of extracellular matrix constituents (44).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, over-expression of miR-21 increases proliferation and reduces apoptosis of VSMC [41]. On the other hand, miR-133 reduces proliferation and migration of VSMC through repressing transcription factor Sp-1 [42], while miR-143/145 inhibits proliferation and increases differentiation of VSMC, leading to repressing neointima formation following carotid artery balloon injury by directly suppressing transcription factor KLF4/5 [37]. Further knockout studies have demonstrated that loss function of the miR-143/145 significantly compromises the contractile phenotype of VSMC [43].…”
Section: Mirnas Regulate Proliferation Migration and Phenotypic Switmentioning
confidence: 98%
“…Brain-targeted ACE2 overexpression attenuated the development of neurogenic hypertension (Ang II infusion: 600 ng/kg per minute for 14 days) and the associated reduction of both SBRS and parasympathetic tone. This prevention of hypertension by ACE2 overexpression was reversed by blockade of the Ang-(1-7) receptor (d-Ala7-Ang- [1][2][3][4][5][6][7]; 600 ng/ kg per minute). Brain angiotensin II type 2 (AT2)/AT1 and Mas/AT1 receptor ratios were significantly increased in SA mice.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Furthermore, vascular microRNA and non-coding RNAs have emerged as major regulators of vessel wall homeostasis and pathologies. [5][6][7][8][9][10][11][12][13] These molecular networks are currently being investigated as specific targets for interventions to prevent and assuage vascular diseases. Since identification of the first specific angiogenic molecule by Folkman and colleagues in 1971, a large number of proangiogenic factors have been identified and characterized.…”
Section: E256 Circulation Researchmentioning
confidence: 99%